Pengaruh Permainan Tradisional Egrang Batok Kelapa Terhadap Perkembangan Motorik Kasar Anak Usia Dini Di Kelompok B TK Padma Mandiri Bandar Lampung Tahun Ajaran 2022/2023 - Juliyanti, Juliyanti; Tohir, Ahmad; Anggraini, Hetty; Qomario, Qomario (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
Gross motor development in early childhood plays an important role in the process of their growth and development, one way to improve gross motor development is through playing. The traditional game of coconut shell stilts has the potential to provide useful motoric stimulus for early childhood. The aim of the study was to determine the effect of the traditional game of coconut shell stilts on gross motor development of group B early childhood at Padma Mandiri Kindergarten Kedaton Bandar Lampung in the 2022/2023 school year. This research is a quantitative research in the form of One-Group Pretest-Posttest Designs experiments. The population of this study amounted to 12 children. Determination of the sample was carried out using saturated sampling, as many as 12 children. Data collection techniques using the method of observation, documentation, and tests. Based on the results of the research and discussion, it can be seen that based on the calculation of the t test, it is obtained that t count is 17.683 which is greater than t table 2.201 and it is determined that Ho is rejected and Ha is accepted because t count > t table, namely 17.683 > 2.201. So it can be proven that there is a significant influence between playing stilts on the gross motor development of children aged 5-6 years.